Relationship of Mobilization With Fecal Impact Events In Post Laparatomy Patients - Dadi Hamdani; Fuzti Fauzia (Jurnal Vocational Nursing Sciences (VNUS), 2019)
Introduction:  In postoperative patients, a patient requires maximum care to support the postoperative wound healing process for healing the patient's healing. The goals of patient care after laparotomy surgery include: Reducing surgical complications, accelerating healing, restoring patient functions as before surgery, maintaining patient self-concept, and preparing patients to go home, this is what makes postoperative patients require maximum care. Objective: This study aims to determine the relationship between mobilization and the incidence of fecal impaction in post-laparotomy patients. Method: the method used observational research, the population of this study was all post-laparotomy patients in the Wijaya Kusuma BLUD RSU Banjar City from July-August 2014 as many as 33 people using the consecutive sampling technique.  Result: The results of statistical tests using the Chi-Square Test obtained a value of 0.000. So, it can be concluded that there is a relationship between mobilization and the incidence of fecal impaction in post-laparotomy patients. Conclusion: There is a relationship between mobilization and the incidence of impacted feces in postoperative patients, and we hope that future researchers can develop broader research with the latest knowledge and more respondents and use experimental methods